MANAGING AND IMPLEMENTING CHANGE SUCCESSFULLY WITH RESPECT TO COVID-19: A WAY FORWARD FOR SMES - Kashif, Muhammad; Asif, Muhammad Uzair; Ali, Ahsan; Asad, Muzaffar; Chethiyar, Saralah Devi Mariamdaran; Vedamanikam, Mohanamerry (PEOPLE: International Journal of Social Sciences, 2020)
The pandemic has changed the way of doing things in the entire world. To survive in situations, we need change. All the organizations are trying their level best to implement change successfully, however, all of them are facing severe issues. The purpose of this study is to identify the major hurdles in implementing change and identifying a way out to cope with the situation based on available literature on SMEs and change management. This study follows a synthesized literature review methodology and is a kind of review paper. In this research, literature that has been written on crisis management and especially over the COVID 19 has been reviewed. In this review analysis, previous studies regarding change management and the importance of SMEs in economic sustainability have been discussed. The paper is a review of existing literature and will identify how the organizations can survive through implementing change successfully. The study is significant for SMEs in the entire world. The study is useful for understanding the issues that are related to managing and implementing change in small and medium enterprises especially while facing contingencies. Finally, in this research, future researchers are guided to empirically test the factors identified in the findings of the study.